Elastic properties and intrinsic strength of two-dimensional InSe flakes. (23rd May 2019) - Li, Yuhao; Yu, Chuanbin; Gan, Yingye; Kong, Yangyang; Jiang, Peng; Zou, Dai-Feng; Li, Penghui; Yu, Xue-Feng; Wu, Rong; Zhao, Huijuan; Gao, Cun-Fa; Li, Jiangyu
Abstract: The mechanical properties of two-dimensional (2D) materials are critical for their applications in functional devices as well as for strain engineering. Here, we report the Young's modulus and breaking strength of multilayered InSe, an emerging 2D semiconductor of the layered group III chalcogenide. Few-layer InSe flaks were exfoliated from bulk InSe crystal onto Si/SiO2 substrate with micro-fabricated holes, and indentation tests were carried out using an atomic force microscopy probe. In combination with both continuum analysis and finite element simulation, we measured the Young's modulus of multilayer 2D InSe (>5 L) to be 101.37 ± 17.93 GPa, much higher than its bulk counterpart, while its breaking strength is determined to be 8.68 GPa, approaching the theoretical limit of 10.1 GPa. Density functional theory calculations were also carried out to explain the insensitivity of Young's modulus to the layer count. It is found that 2D InSe is softer than most 2D materials, and exhibits breaking strength higher than that of carbon fiber, yet remaining more compliant, making it ideal for flexible electronics applications. The reliability of our method is also validated by measurement of graphene.